Kissssss : A Miscellany - Katz, Steve, 1935- (Book collections on Project MUSE., 2007)
A collection of short stories that employ a variety of forms - genres, anti-genres, fantasies, games - while highlighting the dangers and delights of contemporary life: Hollywood, tsunamis, war, the art world, AIDS, ambition, weapons of mass destruction, family values, perverse sexualities, urban violence, small change and big bucks.